No evidence of local deforestation leakage from protected areas establishment in Brazil's Amazon and Atlantic Forest. (September 2022) - de Assis Barros, Luizmar; Venter, Michelle; Ramírez-Delgado, Juan Pablo; Coelho-Junior, Marcondes G.; Venter, Oscar
Abstract: Establishing Protected areas (PAs) could displace or cause 'leakage' of deforestation into adjacent areas. Such leakage would potentially offset PAs' conservation effort by jeopardizing forest conservation goals and impeding financial mechanisms such as Reducing Emissions from Deforestation and forest Degradation - REDD+. Here we investigate forest loss inside PAs' borders and whether leakage occurred following the establishment of new PAs ( n = 425) within the Amazon and the Atlantic forests in Brazil between 2004 and 2017. We applied a Before-After-Control-Intervention statistical design with a matching approach to evaluate deforestation leakage from PAs' establishment using a spatial (inside and outside PAs)– temporal (before and after PA establishment) measure of deforestation rates. We also used "Random Forest" to investigate the drivers of the effect of PAs' establishment on their surrounding areas. We found that when PAs' establishment led to reducing deforestation inside their boundaries, their surrounding also experienced a reduction in deforestation ("blockage"). Similarly, when PAs' establishment could not reduce deforestation inside their boundaries, their surroundings also experienced increased deforestation. Such a pattern was most common for Indigenous territories, especially in the deforestation arch in the Amazon. However, we did not find significant evidence for leakage as PAs' surroundings with a significant increase in deforestation were associated with PAs unable to significantly reduce deforestation within their boundaries. Therefore, "leakage" should not limit the establishment of new PAs. Instead, greater investments into reinforcement are needed for existing PAs, with high priority given to Indigenous Territories. Highlights: Using a Before-After-Control-Intervention approach, we assessed spatio-temporal deforestation leakage from 425 Brazilian protected areas (PAs). Brazilian PAs established from 2004 to 2017 showed no significant evidence of deforestation leakage. Evidence for 'blockage' was found in all PAs types (Strict protection, Sustainable use, and Indigenous territories) in both Biomes. Most of the PAs with the highest priority for reinforcement are the Indigenous territories in the Amazon and Atlantic Forest. Multi-level governance efforts are required to support PAs and reinforce their role in biodiversity conservation and multiple ecosystem services provision.